Introducing Nafion for In Situ Desalting and Biofluid Profiling in Spray Mass Spectrometry - Song, Xiaowei; Mofidfar, Mohammad; Zare, Richard N. (Frontiers in Chemistry, 2022)
We introduce Nafion into the ambient ionization technique of spray mass spectrometry to serve for in situ desalting and direct analysis of biological fluids. Nafion was coated onto the surface of the triangular spray tip as the cation exchange material. Because the sulfonic group from the Nafion membrane effectively exchanges their carried protons with inorganic salt ions (e.g., Na+ and K+), the analyte’s ionization efficiency can be significantly enhanced by reducing ion suppression. The desalting efficiency can reach 90% and the maximum tolerance of the absolute salt amount reaches 100 μmol. The mass spectral profile can also be simplified by removing the multiple adducted ion types from small-molecule drugs and metabolites ([M + Na]+ and [M + K]+), or multiply charged ions formed by proteins ([M + nNa]n+ and [M + nK]n+). Thus, the Nafion coating makes less ambiguous data interpretation collected from spray mass spectrometry for qualitative profiling or quantitative measurement of a target analyte.